Eine neue Prägung : Innovationspotentiale von Münzen in der griechisch-römischen Antike. - Eckhardt, Benedikt (Philippika., 2016)
The contributions in this volume are related to the role coins could play in ancient societies, especially Greek societies. Although the articles approach the subject of coins from different perspectives, all are rooted in concrete case studies and seek to understand how coins could serve as the harbingers of innovation, the medium of representation, how coins conveyed new social practices and the effects that coins could have within and beyond the economic field.